Knowledge, Attitude and Practice towards Family Planning among the Reproductive Age Group of Married Women in Semi Urban Area - Kumar Yadav, Amar; Acharya, Alok; Mishra, Rimu (Journal of Nobel Medical College, 2022)
Background: Knowledge of contraceptive methods is nearly universal in Nepal, with almost all women and men knowing at least one method of contraception. The contraceptive prevalence rate among currently married women age 15-49 is 53%, with 43% using modern methods.  This implies that Nepal needs to strengthen its family planning program to achieve the country’s commitments to global family planning goals and to reach a modern contraceptive prevalence rate of 52% by 2020.Materials and Methods: The study was descriptive cross sectional community based conducted in kharji, biratnagar municipality ward number 4, semi urban area or Eastern zone of Nepal. Total female of reproductive age 15 -49 married women 473 taken as a sample size. The data were collected by interview by predesigned and pretested questionnaire. Analysis of the data was done by SPSS.Results: Among all the respondents, 453 (95.77%) had the knowledge about the family planning.  The majority of the study population 430 (90.90%) had positive attitude towards contraceptives. Among the all respondents, 210 (44.39%) were practice the different types of contraceptives methods. Most of the respondents 75(35.71%) practiced condom.Conclusion: The study concludes that the married women of reproductive age group had good knowledge and positive attitude towards family planning even though the practiced of family planning were low (44.39%).